Exploring Knowledge and Attitudes About Human Papillomavirus Vaccination Among School Nurses in an Urban School District. (13th December 2020) - Selvan, Preethi; Kearney, Matthew; Cognetti, David; Massey, Philip; Leader, Amy
ABSTRACT: BACKGROUND: Nurses in an urban school district completed a brief survey about their knowledge, attitudes, and practices related to human papillomavirus (HPV) vaccination. METHODS: Descriptive and bivariate analyses examined trends and differences. RESULTS: Among 208 nurses, only 3% correctly answered all 5 knowledge questions. Nurses with greater than 10 years of experience were more confident about where to refer a student for vaccination (p < .01) and less likely to be interested in providing the vaccine at their school (p < .001) compared to those with less than 10 years of experience. Almost one third (32%) of nurses reported having access to educational material about the HPV vaccine at their schools. CONCLUSIONS: Whereas most nurses had positive attitudes about the vaccine, fewer were interested in administering the HPV vaccine in school. Educational resources for school nurses could increase awareness of the vaccine and promote linkages to care outside of school.